Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The degree of the secondary school teacher using the Madrasati platform in education in Al-Baha region Mr. Fahed Salem AlRobai, Prof. Muhammad Hassan Al Sofran 2. The Effectiveness of the Electronic Collabortion Learning for Developing the Mathematical Proficiency among Pre-service Mathematics Teachers Mrs. Shohwd Sharaf Gharsan Sallam, Prof. Radman Mohamed Saeed 3. Extant virtual lab. technology is used in teaching chemistry course in secondary schools in inclusive learning environment from the teachers’ perspectives Teacher Mona Mafarh D. Al-Harhty, Co-Prof. Hanan Abdul Rahman Al-Arini 4. Emotional intelligence and its relationship to the performance level of early childhood teachers in Hafr Al-Batin region, Saudi Arabia Mrs. Nada Remthan Al-Mukhtari Al-Shammari 5. Dimensions of academic procrastination and its relationship to perceived self-efficacy among first-year undergraduate students at King Saud University Co-Prof. Elsayed R, Boriek 6. The Motivational Design of Digital learning Platforms using the (ARCS) Model and its Effectiveness in developing the Reading Comprehension among Middle School Students Mr. Adnan Hassen Alobaidi, Prof. Ashraf Ahmed Zeidan 7. Locus of control and its relationship to prejudice attitudes among Tafila Technical University students’ Mrs. Saida H. Al-Qaisi, Prof. Ahmed M. Thawabieh